2008
DOI: 10.1002/bip.21130
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of binding selectivities and affinities of platinum‐based quadruplex interactive complexes by electrospray ionization mass spectrometry

Abstract: The quadruplex binding affinities and selectivities of two large π-surface PtII phenanthroimidazole complexes, as well as a smaller π-surface platinum bipyridine complex and a larger RuII complex, were evaluated by electrospray ionization mass spectrometry. Circular dichroism (CD) spectroscopy was used to determine the structures of various quadruplexes and to study the thermal denaturation of the quadruplexes in the absence and presence of the metal complexes. In addition, chemical probe reactions with glyoxa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 71 publications
0
40
0
Order By: Relevance
“…Combining ESI-MS with the use of chemical probes (57,58) that react with and modify nucleic acids in a structure-dependent manner provides a more versatile approach to investigating ligandbinding sites and understanding how interactions of ligands with DNA can alter its conformation. Chemical probes in conjunction with ESI-MS have been used for both RNA and DNA substrates (44,(59)(60)(61). Investigation of the impact of ligand binding on DNA conformations was first reported for reactions of KMnO 4 , an oxidizing agent that reacts primarily by attacking the double bond of thymine to produce a mixture of diol and an alpha-hydroxylketone product, which leads to product mass shifts of 34 and 32 Da, respectively (Figure 10) (61).…”
Section: Use Of Chemical Probes To Characterize Dna/ligand Complexesmentioning
confidence: 99%
See 2 more Smart Citations
“…Combining ESI-MS with the use of chemical probes (57,58) that react with and modify nucleic acids in a structure-dependent manner provides a more versatile approach to investigating ligandbinding sites and understanding how interactions of ligands with DNA can alter its conformation. Chemical probes in conjunction with ESI-MS have been used for both RNA and DNA substrates (44,(59)(60)(61). Investigation of the impact of ligand binding on DNA conformations was first reported for reactions of KMnO 4 , an oxidizing agent that reacts primarily by attacking the double bond of thymine to produce a mixture of diol and an alpha-hydroxylketone product, which leads to product mass shifts of 34 and 32 Da, respectively (Figure 10) (61).…”
Section: Use Of Chemical Probes To Characterize Dna/ligand Complexesmentioning
confidence: 99%
“…The interactions of three platinum-based complexes-bipyridine ethylenediamine platinum(II) (Pt1), phenylphenanthroimidazole ethylenediamine platinum(II) (Pt2), and naphthylphenanthroimidazole ethylenediamine platinum(II) (Pt3) (see Figure 9)-with quadruplex DNA were evaluated by ESI-MS (44). These complexes were designed to incorporate extended aromatic pi surface areas to enhance their end-stacking interactions with quadruplex DNA.…”
Section: Electrospray Ionization Mass Spectrometry Analysis Of Quadrumentioning
confidence: 99%
See 1 more Smart Citation
“…In order to clearly illustrate the binding affinities of small molecules (P1-P12) to the G-quadruplex (G4), a parameter, IRa [18][19][20][21], is introduced as the intensity ratio of all complex ions The IRa value is 1.00 when all the G-quadruplex ions are binded with small molecules. The closer the IRa value to 1.00, the higher the binding affinity of small molecules to the G-quadruplex.…”
Section: Small Molecules Bind To the G-quadruplexmentioning
confidence: 99%
“…Phan and coworkers studied the structure of this G-rich sequence in K + solution by NMR spectroscopy, and found that this G-rich sequence can form a G-quadruplex containing three G-tetrad layers [15]. In this study, we used electrospray ionization mass spectrometry (ESI-MS) and circular dichroism (CD) spectroscopy [16][17][18][19][20][21] to probe the formation and recognition of the G-quadruplex from d(A 1 GGGA 5 GGGCG 10 CTGGG 15 AGGAG 20 GG) (named as S1) in the promoter region of human c-kit oncogene.…”
Section: Introductionmentioning
confidence: 97%